Limit distribution of the number of solutions of a system of random Boolean equations with a linear part - Masol, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove two theorems on the Poisson limit distribution of the number of solutions of an a priori consistent system of nonlinear random Boolean equations with stochastically independent coefficients. In particular, we assume that this system contains a linear part.